Effects of basic medical insurance integration on subjective wellbeing of residents in China: empirical evidence from a quasi-experiment - Na, Xin; Ding, Lingzhi; Wang, Junxia; Chu, Shuzhen (Frontiers in Public Health, 2023)
Thank you for giving us the opportunity to submit a revised draft of our manuscript entitled "Effects of Basic Medical Insurance Integration on Subjective Well-being of Residents in China: Empirical Evidence from a Quasi-experiment". We appreciate the time and effort that you and the reviewers have dedicated to providing your valuable feedback on our manuscript.We are grateful to the reviewers for their insightful comments on our paper. We have been able to incorporate changes to reflect most of the suggestions provided by the reviewers, and we have highlighted the revisions within the manuscript with tracked changes.After considering the contributions of each author to the revisions, it has been determined that Xin Na and Lingzhi Ding contributed equally to this work and will share first authorship.We also included a response to reviewers in which we addressed comments the reviewers made, we hope that these modifications can fulfill the requirements to make the manuscript acceptable for publication. Please let us know if you have any concerns about the manuscript and we would like to address them as soon as possible.Thank you again for your consideration of the revised manuscript.